On German Unity - Olboeter, H. (Scientia Militaria - South African Journal of Military Studies, 2012)
On 3 October 1990 the division of Germany into two states came to an end. The German Democratic Republic (GDR) acceded to the Federal Republic of Germany and in doing so ceased to exist. This epoch-making event took place peacefully and in agreement with all Germany’s friends, allies and European neighbours. United at the heart of Europe, Germany gained full sovereignty over its internal and external affairs. Thus, after 40 years of division, a victory was won by the feeling of solidarity and the wish of the people in both parts of Germany to live together in one country that guarantees freedom, democracy and the rule of law.